Comparative evaluation of Mangifera indica leaf mouthwash with chlorhexidine on plaque accumulation, gingival inflammation, and salivary streptococcal growth - Sham S Bhat; K Sundeep Hegde; Chinchu Mathew; S Vidya Bhat; M Shyamjith (Wolters Kluwer Medknow Publications, 2017)
Aims: This study aims to compare the efficacy of a mango (Mangifera indica) leaf mouthwash with chlorhexidine on plaque status, gingival status, and salivary Streptococcus mutans count. Materials and Methods: A sample of twenty children, aged 8-14 years, Mangalore Residential School, Karnataka, India, was allocated into two groups. Group A (10) and Group B (10) were given test mouthwash "mango leaf mouthwash" and chlorhexidine, respectively. The clinical trial was carried out for ½ h after rinsing and after 5 days, during which children were asked to rinse once daily, with 10 ml of the given mouthwash ½ h after tooth brushing. Results: There was a significant reduction in microbial count, improved plaque control and gingival health in mango leaf and chlorhexidine mouthwash groups with higher reduction in microbial count, and better plaque control and gingival health seen in chlorhexidine group. Conclusion: Herbal alternatives proved to be an effective and safe alternative to conventional modes of treatment.